2018
DOI: 10.1002/fut.21938
|View full text |Cite
|
Sign up to set email alerts
|

Price discovery in the Chinese gold market

Abstract: This study conducts price discovery analysis in the Chinese gold market. Our results indicate that Chinese gold market price discovery occurs predominantly in the futures market. The result is robust to numerous different measures of price discovery, namely, information share, component share, and information leadership share. Partitioning the daily trades into three trading sessions, we find that the dominance of the futures market occurs consistently in all trading sessions. Furthermore, we investigate seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 43 publications
(99 reference statements)
1
11
0
Order By: Relevance
“…Table 5 documents the CS and IS for the different sampling intervals. In line with Jin et al (2018), price discovery shares get closer to 0.5 when lower‐frequency intervals are used, on average. Stated differently, the differences in price discovery shares between the spot and futures market are less when increasing time‐intervals (see Tse, Xiang, & Fung, 2006, for similar results).…”
Section: Price Discoverysupporting
confidence: 86%
See 3 more Smart Citations
“…Table 5 documents the CS and IS for the different sampling intervals. In line with Jin et al (2018), price discovery shares get closer to 0.5 when lower‐frequency intervals are used, on average. Stated differently, the differences in price discovery shares between the spot and futures market are less when increasing time‐intervals (see Tse, Xiang, & Fung, 2006, for similar results).…”
Section: Price Discoverysupporting
confidence: 86%
“…Brandvold et al (2015) and Jin, Li, Wang, and Yang (2018) point out that it is important to keep time intervals short enough to ensure information is not lost between sampling intervals, but also long enough to avoid noise due to stale prices. Following Jin et al (2018), we consider various sampling frequencies. In particular, we compute the nonsynchronous quoting probability, as well as the frequency of zero‐returns as zero‐returns are an important indicator of liquidity differences between spot and futures markets (see Theissen, 2012).…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In the study on the relationship between spot and futures prices in commodity markets (corn, wheat, soybeans, soybean meal and oil, feeder, and live cattle) Dimpfl et al ( 2017 ) find evidence that the prices of these commodities are almost uniquely formed in the spot market and the contribution of the futures contracts to price discovery is less than 10%. Jin et al ( 2018 ) examine the price discovery of Chinese gold spot and futures markets and concluded that the Chinese gold market's price discovery occurs predominantly in the futures market. Miao et al ( 2017 ) investigate the price discovery process between the CSI 300 equity index and index futures in China.…”
Section: Literature Reviewmentioning
confidence: 99%